The Association Between Loneliness and Depression in Adolescents with Self-harm at a Vocational High School in Kabupaten Malang - Puspa Maharani; Izzatul Fithriyah; Ivana Sajogo (Faculty of Medicine, Universitas Airlangga, 2024)
Introduction: Adolescents with self-harm behavior are in the spotlight because they are increasing nowadays. Various studies have shown a relationship between self-harm and affective disorders, one of which is depression. Adolescents are also subjects who are prone to feeling lonely. This study was conducted to determine the association between loneliness and depression in adolescents with self-harm behavior at Vocational High School in Kabupaten Malang. Methods: This study used an observational analytic cross-sectional study design with a consecutive sampling technique. The population and sample were students in the 10th and 11th grades (14-18 years old) at a Vocational High School in Kabupaten Malang. Self-harm behaviors are questioned using the Self-Harm Inventory (SHI). Loneliness levels are measured using the UCLA Loneliness Scale Version-3 (UCLA-3). Meanwhile, depression rates are evaluated using the Patient Health Questionnaire -9 (PHQ-9). Statistics will be tested using Chi-square analysis. Results: Approximately 25% of subjects tended to do self-harm, and 101 of them had mild symptoms of depression. The results of the chi-square independence test showed that χ2(4)=253.663 p=0.000. A moderate degree of loneliness was experienced by 32.31% of students or as many as 95 students. The chi-square independence test showed that χ2(3)=216.359 p=0.000. Discussion: Few research, nevertheless, have painted a picture of adolescent loneliness, suggesting that both loneliness and depression may be risk factors for young people to harm themselves. This study showed a strong correlation between loneliness and self-harm. Conclusion: There was a significant correlation between self-harm, depression and loneliness. Keywords: Loneliness, Self-Harm, Depression, Adolescent, Mental Health